What correlates with persistence of women in physics? - Maxwell Franklin; Eric Brewe (Physical Review Physics Education Research)
This study uses an initial attitudinal survey and a subsequent follow-up survey to assess which qualities are correlated with the persistence of women in physics. The initial survey was given to participants at the Conference for Undergraduate Women and Gender Minorities in Physics, and the follow-up survey was given years later, after they graduated; 478 matched surveys were used in this work. Using these surveys, we study how attitudes correlate with retention. First, we examine whether affective factors, mainly situated in identity theory, have any clear correlation with persistence in physics. Then, we study individual questions of the survey, such as a student’s interest in research specifically, to determine more fine-grained correlations with retention. Both of these were examined using analyses of variance (ANOVAs) with post hoc Tukey tests. From studying the overarching factors, we find that respondents who remained in physics after completing their bachelor’s degree reported higher interest than respondents who left physics at earlier points, with a medium effect size. We also find small evidence of associations between sense of belonging and correlation; respondents who leave physics before obtaining a bachelor’s degree tend to have a higher sense of belonging than other groups, while respondents who stay in physics until graduating, then leave for another science, technology, engineering, and mathematics field tend to have a lower sense of belonging. This association, however, shows a small effect size and should be examined more carefully to draw definitive conclusions. We find that identity, perceived recognition, performance competence, success mindset, and sense of community show no significant correlation with long-term persistence. When examining individual questions, we find that people who remain in physics tend to have a higher interest specifically in research, as well as career aspirations of going to graduate school and becoming a professor in physics.